Proof of concept of fully automated adaptive workflow for head and neck radiotherapy treatments with a conventional linear accelerator - Muti, Gaia; Felisi, Marco M. J.; Monti, Angelo F.; Carsana, Chiara; Pellegrini, Roberto; Salmeri, Edoardo; Palazzi, Mauro; Colombo, Paola E. (Frontiers in Oncology, 2025)
IntroductionThe objective of this study is to evaluate the performance of an automatic workflow for head-and-neck (H&N) radiotherapy using a multi-atlas based auto-contouring software and an a-priori multicriteria plan optimization algorithm and implement an adaptive online approach with CBCT images. Two different modalities are investigated, the fluence-to-position (FTP) and the adapt-to-shape (ATS) approach.Materials and methodsNine patients are used for the multi-atlas database. The organs at risk (OARs) of the H&N district and five additional structures (air, fat, tissue, bone and patient’s exterior) subsequently used for the creation of the synthetic CT are auto-contoured with the Elekta ADMIRE® software. The mCycle algorithm is used for the a-priori multicriteria plan calculation. A total of twenty H&N patients are selected for this step. The automatic plans are compared to manual VMAT plans by assessing differences in planning time, dose delivered to targets and OARs, and calculating the plan quality indexes (PQIs). Two patients are chosen for the retrospective CBCT adaptive online feasibility analysis. To assess the differences for the two adaptive modalities, the clinical goals for targets and OARs and the number of passed constraints are explored. An analysis of the timing for the different steps is carried out to assess its clinical applicability.ResultThe dice of the five HU layer structures range between 0.66 and 0.99. The mCycle auto-planning significantly reduces planning time, from 2 hours to 10 minutes. The radiotherapist deems all plans clinically acceptable, and in the majority of cases the automatic plan is the preference choice. The automatic plans enhance OARs sparing and preserve a good target coverage, this is also confirmed by the PQIs result. Comparing FTP and ATS modes in adaptive radiotherapy, ATS exhibits superior outcomes, mostly in the target coverage. In the FTP techniques target coverage is inadequate and statistically different from the accepted values. In the ATS the results align with the initial approved values. Using the ATS mode the planning time takes around 14 minutes and approximately 20 minutes for the entire treatment.ConclusionThis study contributes to the advancement of automatic and adaptive radiotherapy, demonstrating the potential of an automated workflow in H&N treatments.